Propolis Extracted Using CMCE Decreases TNF–α and C-Reactive Protein level of CCl4- Induced Liver Damage in Rats - Saputro, Arief Adi; Nasihun, Taufiqurrachman; Hussaana, Atina (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2021)
Introduction: Carbon tetrachloride (CCl4) is a hepatotoxic substance inducing inflammation in liver cells. Inflammation is marked by increase in proinflammatory cytokines level such as tumor necrosis factor alpha (TNF-α), and C-reactive protein (CRP) produced by hepatocytes. Propolis extracted using continuous multi-stage countercurrent Extraction (CMCE propolis extract) contains active balsamic, caffeic acid phenetyl ester (CAPE), and flavonoids capable of affecting pro-inflammatory cytokines. Objective: to investigate the effect of CMCE propolis extract on TNF-α and CRP levels in CCl4-induced liver damage.Methods: In this study using a post test only control group design, 28 male Wistar rats were divided into four groups. The control group (C-G) was given CCl4 0.4 ml/200 g on day 14. The P3-G, P7-G, P14-G groups were treated with 3.6 mg/200 g, 7.2 mg/200 g, 14.4 mg/200 g CMCE propolis extract for 14 days and given CCl4 0.4 ml/g on day 14. The TNF-α and CRP levels were assessed using the ELISA kit one-way ANOVA and Post Hoc test (LSD) were applied for the statistical analysis. Results: TNF-α level in P14-G group (3.26 ± 0.93), P7-G (6.17+0.78), and P3-G (10.4±1.34) were significantly lower than that of C-G (17.29+1.56) (p<0.05). CRP levels in P14-G group (0.61±0.09), P7-G (1.38+0.48), and P3-G (12.01±0.65) were significantly lower than those of C-G (2.95+0.668) (p<0.05). The greatest reduction in TNF-α & CRP level was found in the group given propolis at a dose of 14.4 mg/200 g.Conclusion: The administration of CMCE propolis extract reduces TNF-α & CRP levels in CCl4-induced liver damage.